Social cognition in South African children with Fetal Alcohol Spectrum Disorders - Lindinger, Nadine Michelle (Department of Psychology, 2016)
Research on the social-cognitive profile of individuals with prenatal alcohol exposure (PAE) has confirmed poorer social skills in these children compared to healthy controls, independent of overall cognitive functioning. However, although children with fetal alcohol spectrum disorders (FASD) are known to have deficits in social-cognitive function, very little is known about the mechanisms underlying these impairments. I investigated social cognition in children with FASD by assessing Theory of Mind and emotion recognition ability as potential determinants of impaired social cognition, behaviourally and using neuroimaging. Study I showed that children aged 9-11 years (N =63) with fetal alcohol syndrome (FAS) and partial FAS performed more poorly on the Reading the Mind in the Eyes test, after controlling for IQ and executive function, suggesting difficulty in inferring people's mental states. Study II investigated the ability of 9-12 year old children (N = 88) to read people's facial emotions because this more basic level of social cue processing was considered a possible precursor to the impairments seen in Study I. An affective appraisal and working memory (WM) task (1- back and 2-back) was administered. Groups performed well on the 1-back, indicating ability to meet WM demands of the affective appraisal task. No behavioural group differences were shown on the affective appraisal task, which confirmed the suitability of this task to identify possible differences in neuronal activation, which I investigated in Study III. Analyses of these fMRI data on 64 children aged 9 -14 years showed that participants performed well on the relatively simple affective appraisal task. However, greater cortical activation was shown in exposed children when processing positive but less when processing negative facial expressions. These data demonstrate that heavy PAE alters activation within a cortical affective processing network. Because we know that children with FASD have alcohol-related social-cognitive impairments (Study I), differences in cortical activation may suggest that when children with FASD need to appraise affect in more challenging contexts, as in dynamic social interactions, they are likely to have greater difficulties. These data are consistent with two ideas: a) that alcohol-exposed children have difficulty appraising negative emotions and b) that difficulty contributes to the clinically described trouble these children have in "reading" facial social cues. If this is true, then an intervention program that improves the ability of these children to appraise negative emotions will likely (a) improve their ability to correctly interpret the context of their social interactions; (b) contribute to developing mental representations of an appropriate reaction to a given situation and (c) positively affect the various evaluation processes during social information processing, which in turn are imperative to social -cognitive functioning.